Bond strength evaluation of corroded steel bars via the surface crack width induced by reinforcement corrosion. (1st December 2017) - Lin, Hongwei; Zhao, Yuxi; Ožbolt, Joško; Reinhardt, Hans-Wolf
Highlights: The surface crack width is closely correlated with the corrosion level. The presence of stirrups can significantly limit the degradation of bond strength. Models for predicting the bond strength based on the surface cracks are proposed. Abstract: The corrosion of steel bars in reinforced concrete structures induces concrete cover cracking and leads to reduction in steel–concrete bond strength. In the present study, a series of pull-out tests were carried out to investigate the potential correlations between corrosion level, surface crack width, and bond strength. The main variables are corrosion level, concrete cover depth, and spacing of stirrups. The test results indicate that the surface crack width is closely linked to the corrosion level of the tensile steel bar, and the crack propagation can be divided into three stages. It is further revealed that the bond strength decreases exponentially with the surface crack width. Based on the test results, an empirical model for estimating the bond strength using the surface crack width is formulated, which considers the pronounced limiting effect of stirrups on the bond degradation. The model is further improved by incorporating the adverse effect of the corrosion of stirrups according to the previous investigations. Comparison with existing experimental database in the literature proves that the proposed models are able to realistically predict the bond strength of corroded steel bars.